Antiplatelet Treatment for Catheter-Based Interventions in High-Risk Patients: Current Guidelines and Expert Opinion - Rath, Dominik; Gawaz, Meinrad (Hämostaseologie, 2018)
Catheter-based interventions have revolutionized treatment of both coronary artery disease and aortic valve disease. Yet, these procedures are accompanied by thromboembolic and bleeding complications. Antiplatelet agents and anticoagulants with tolerable risk of bleeding complications are required to protect from recurrent thromboembolic events. Although guidelines for antithrombotic treatment in patients undergoing percutaneous coronary intervention (PCI) and transcatheter aortic valve replacement (TAVR) are available, scarce evidence exists regarding therapeutic recommendations for patients at high risk for thromboembolic events or major bleeding. The choice of optimal antiplatelet therapy after PCI in patients with complex coronary artery disease and concomitant atrial fibrillation often poses a clinical challenge. The antiplatelet therapy in patients undergoing TAVR is so far based mostly on expert consensus. The present review addresses state-of-the-art antithrombotic therapy, particularly focusing on patients at high risk of thromboembolic and bleeding events, and aims to provide recommendations for clinical practice.
Keywords: PCI; TAVR; atrial fibrillation; antiplatelet therapy